Excess risk of preterm birth with periconceptional iron supplementation in a malaria endemic area: analysis of secondary data on birth outcomes in a double blind randomized controlled safety trial in Burkina Faso - Bernard Brabin (Malaria Journal, 2019)
Abstract Background Iron supplementation before a first pregnancy may improve the future health of mother and baby by reducing maternal anaemia. Iron supplementation could, however, increase malaria infections, notably in primigravidae who are most susceptible. The pathogenicity of other iron-utilizing pathogens could also increase, causing inflammation leading to increased risk of adverse birth outcomes. This paper reports pre-specified secondary birth outcomes from a safety trial in Burkina Faso in an area of high malaria endemicity. Primary outcomes from that trial had investigated effects of long-term weekly iron supplementation on malaria and genital tract infections in non-pregnant and pregnant women. Methods A double-blind, randomized controlled trial. Nulliparous, mainly adolescent women, were individually randomized periconceptionally to receive weekly either 60 mg elemental iron and 2.8 mg folic acid, or 2.8 mg folic acid alone, continuing up to the first antenatal visit for those becoming pregnant. Secondary outcomes were ultrasound-dated gestational age, fetal growth, placental malaria, chorioamnionitis and iron biomarkers. Seasonal effects were assessed. Analysis was by intention to treat. Results 478 pregnancies occurred to 1959 women: 258/980 women assigned iron and folic acid and 220/979 women assigned folic acid alone. Malaria prevalence at the first antenatal visit was 53% (iron) and 55% (controls). Mean birthweight was 111 g lower in the iron group (95% CI 9:213 g, P = 0.033). Mean gestational ages were 264 days (iron) and 269 days (controls) (P = 0.012), with 27.5% under 37 weeks compared to 13.9% in controls (adjRR = 2.22; 95% CI 1.39–3.61) P < 0.001). One-third of babies were growth restricted, but incidence did not differ by trial arm. Half of placentae had evidence of past malaria infection. C–reactive protein > 5 mg/l was more common prior to births < 37 weeks (adjRR = 2.06, 95% CI 1.04–4.10, P = 0.034). Preterm birth incidence during the rainy season was ~ 50% in the iron arm and < 20% in controls (P = 0.001). Chorioamnionitis prevalence peaked in the dry season (P = 0.046), with no difference by trial arm (P = 0.14). Conclusion Long-term weekly iron supplementation given to nulliparous women in a malaria endemic area was associated with higher risk of preterm birth in their first pregnancy. Trial Registration NCT01210040. Registered with Clinicaltrials.gov on 27th September 2010